HUBUNGAN FAKTOR INDIVIDU DENGAN KEJADIAN GANGGUAN PERNAPASAN DI PT. PERINDUSTRIAN DAN PERDAGANGAN KARET BANGKINANG TAHUN 2018 - Lira Mufti Azzahri (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2018)
Every workplace always contains various potential hazards that can affect the health of the workforce can cause health problems. One of the entrances or entrance of a substance into the human body through the respiratory system. The rubber industry is one of the working environments which is hazardous to lung health. Exposure received by workers in an industrial activity consists of: chemical, physical and biological exposure. In the rubber industry, workers are more often exposed or exposed to chemical exposure, one of which is ammonia. The purpose of this study was to determine the factors associated with respiratory disorders in PT. Bangkinang Rubber Industry and Trade in 2018. The study used a quantitative design using cross sectional, the sample in this study was 125 respondents, the sampling technique was the total population, data collection using observation sheets and questionnaires, data analysis using Chi Square. Statistical test results can conclude the relationship of work period (p = 0,000), there is a relationship of age (p value = 0.002), and there is a relationship between the use of PPE (p = 0,000) with respiratory safety events at PT. Bangkinang Rubber Industry and Trade. This study discusses socialization and counseling about the replacement of respiratory disorders in workers.